2012
DOI: 10.3892/ijo.2012.1671
|View full text |Cite
|
Sign up to set email alerts
|

CD82 inhibits canonical Wnt signalling by controlling the cellular distribution of β-catenin in carcinoma cells

Abstract: We have recently unravelled a novel function for CD82 in E-cadherin-mediated cellular adhesion. CD82 inhibits β-catenin tyrosine phosphorylation and stabilizes E-cadherin-β-catenin complexes at the cell membrane. This function inhibits cancer cell dissociation from the primary cancer nest and limits metastasis. In this study, we focused on the effect of CD82 on the Wnt/β-catenin (canonical) pathway, which controls the cellular distribution of β-catenin. CD82 had no effect on the expression of Wnt proteins but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
(51 reference statements)
3
20
0
Order By: Relevance
“…7C). Cortical ␤-catenin has been shown to be stabilized by CD82-mediated inactivation of GSK-3␤ and casein kinase 1␣ (21). We observed a slight, but not significant, decrease in phospho-GSK-3␤ (Ser-9) levels in E-cadherin antibody-treated cells, compared with control cells, and the total GSK-3␤ protein levels were unchanged by these treatments (data not shown).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 47%
See 1 more Smart Citation
“…7C). Cortical ␤-catenin has been shown to be stabilized by CD82-mediated inactivation of GSK-3␤ and casein kinase 1␣ (21). We observed a slight, but not significant, decrease in phospho-GSK-3␤ (Ser-9) levels in E-cadherin antibody-treated cells, compared with control cells, and the total GSK-3␤ protein levels were unchanged by these treatments (data not shown).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 47%
“…The transmembrane cell adhesion molecule, E-cadherin, is a major component of adherens junctions in epithelial and other cell types (17)(18)(19) that recruits ␤-catenin and results in the coupling of E-cadherin to the Wnt pathway. The binding of ␤-catenin to type I cadherins renders a stable pool of membrane-bound ␤-catenin that regulates and stabilizes these cell-cell contacts (20,21). High resolution analysis has allowed understanding of the elaborate cell adhesion complex that includes cadherins, catenins, and the F-actin network (22).…”
mentioning
confidence: 99%
“…The cellular localization and accumulation of β‐catenin are known to be tightly regulated by Wnt proteins. In the absence of Wnt, β‐catenin is phosphorylated by GSK‐3β, resulting in its phosphorylation, ubiquitination, and proteasomal degradation (Buescher and Phiel, 2010; Chigita et al ., 2012; Takahashi‐Yanaga, 2013). In the presence of Wnt, β‐catenin is activated through the canonical Wnt pathway and ultimately leads to GC progression (Clevers and Nusse, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A body of evidences indicates that CD82 inhibits migration and invasion by strengthening the cell adhesion, and weakening cellular protrusion and mobility [38][39][40][41][42][43]. Reportedly, CD82 overexpression down-regulated VEGF-C expression via Src/STAT3 pathway in pancreatic cancer cell [36] and sLea/x expression via the downregulation of ST3GAL4 expression to thereby reduce the adhesion of cancer cells to blood vessels [37].…”
Section: Discussionmentioning
confidence: 99%
“…CD82 suppressed HIF-1α and VEGF expression by blocking CDCP1-enhanced Src activation in prostate cancer [40], HGF-induced migration of hepatoma cells via upregulation of Sprouty2 [41] or the inactivation of small GTP-binding proteins of the Rho family via c-Met adapter proteins [42]. Chigita et al [43] concluded that CD82 attenuated Wnt signaling by inhibition of β-catenin nuclear translocation by down-regulation of Fzd receptor proteins, accumulation of β-catenin at the cell membrane by down-regulation of GSK-3β and CK1α, and stabilization of the E-cadherin-β-catenin complex. To investigate the clinicopathological and prognostic significances of CD82 expression, we analyzed 26 studies, which met specific inclusion criteria and had moderate to high quality according to their NOS scores.…”
Section: Discussionmentioning
confidence: 99%